Misturas de óleos essenciais e seus compostosmajoritários na conservação de apresuntados inoculados com Clostridium sporogenes - Simões, Luara Aparecida (2016)
The aim of this study was to evaluate the in vitro antimicrobial effect of different combinations of essential oils of cinnamon, clove and oregano, as well as their compounds majority cinnamaldehyde, eugenol and carvacrol on Clostridium sporogenes vegetative cells inoculated into pressed hams. It was evaluated the effect of these compounds on the residual nitrite concentration, pH, lipid oxidation, color and water activity of the prepared pressed hams. The determination of the Minimum Bactericidal Concentration (MBC) was performed using the broth dilution method. Microbiological analyzes were performed after 24 hours; 7, 21, 14 and 28 days of storage, the pressed ham were stored at 7° and 14° C, while for the physical-chemical analysis the pressed ham were stored at 4° C and analyzed after 24 hours and 30 days of processing. The essential oil of cinnamon and its major compound cinnamaldehyde were the most efficient for the inhibition of vegetative cells of C. sporogenes, presenting lower CMB. Regarding the cell counting, the highest value of C. sporogenes were for the control containing 75 ppm nitrite (TRAT2). There was a diminishing in the bacterial growth over time in the treatments containing oils and compounds with a reduction of approximately 3 log cycles. During 14 days of storage, it was not registered presence of spores in the treatments with essential oils and compounds, resulting in lower average number of spores. The reduction of residual nitrite was approximately 54% for TRAT 1, and 32-39% for others. Regarding color, all treatments showed an increase in luminosity, index a *, index b * and C* saturation. Just the hue (h *) decreased during storage, only for the parameter b * and hue h * there was significant difference between treatments. Treatments containing essential oils and majority compound had a higher lipid oxidation compared with controls. The pH of all pressed ham did not differ statistically. At the end of storage, there was an increase in water activity for all treatments. Therefore, we can conclude that the pressed ham added with essential oils and majority compounds were effective in reducing significantly the number of vegetative cells of C. sporogenes over 28 days of storage. The organism sporulation was delayed showing only minimal changes in the color of the pressed ham. In conclusion, the essential oils and major compounds may have great applicability as a natural preservative in pressed ham.